Analysis of the Multinational Policies of the Han-Zhao State in Ancient China - Congrong Xiao; Yan Zhang; Dongkwon Seong (Genealogy)
The Han-Zhao state (also known as “Former Zhao”, 304–329 AD), founded by Liú Yuán, the Left Wise King of the Xiongnu, is one of the earliest examples of a dual monarchy in global history. Its structure represents not only the fusion of the cultures of the Sinicized Xiongnu rulers and the Han Chinese of the Central Plains, but also the joint governance of a minority regime and the Han Chinese civilization. As an early dual monarchy, the Han-Zhao state implemented a political, military, and cultural system that maintained the coexistence of the Xiongnu traditions and Han Chinese dominance, thereby making it a “dual monarchy”. Thus, while Han-Zhao preserved the traditional governance model of the Xiongnu, it was deeply influenced by Han Chinese rituals and principles of governance. This study analyzes the ethnic and cultural institutions of the Han-Zhao state to explore its uniqueness as a dual monarchy and its influence on the integration of multi-ethnic regimes in later periods. It seeks to enrich the global understanding of the concept of dual monarchy and provide a new perspective on ethnic integration and cultural governance in Chinese history.